22.4k views
4 votes
Please help me solve these answers its already in the morning and I havent goten sleep lol

Please help me solve these answers its already in the morning and I havent goten sleep-example-1
User Gkunz
by
4.6k points

2 Answers

1 vote

Answer:

Explanation:

1. (2x- 1)(x + 7) = (x - 7)(x + 3)

2x^2 + 14x - x - 7 = x^2 + 3x - 7x - 21 =

2x^2 + 13x - 7 = x^2 - 4x - 21 =

2x^2 + 13x = 7 x^2 - 4x = 21

2. 6x^5 + 15x^2 = 8x^4 - 6x =

3x^2(2x^3 + 5) 2x(4x^3 - 3)

3. 6x^2 + 15x + 9 = 14x^2 - 18x + 4 =

3(2x^2 + 5x + 3) = 2(7x^2 - 9x + 2) =

3(2x + 3)(x + 1) 2(7x - 2)(x - 1)

4. 3x^2 + 2x - 1 = x^2 + 10x + 16 =

(3x - 1)(x + 1) (x +2)(x + 8)

User RRikesh
by
4.4k points
4 votes
Hope this helps ya! :)
Please help me solve these answers its already in the morning and I havent goten sleep-example-1
User Manoj Savalia
by
4.6k points